2014
DOI: 10.1016/j.egypro.2014.11.1136
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Energy Storage Performances of Methane Reforming with Carbon Dioxide in Tubular Packed Reactor

Abstract: High temperature heat transfer and energy storage characteristics of methane reforming in tubular packed reactor are investigated under different operating temperature and inlet conditions. Experimental results show that the methane reforming in tubular packed reactor can efficiently storage high temperature thermal energy, and the thermochemical storage, sensible heat increment and heat loss are all very important. As the operating temperature increases, the thermochemical storage efficiency first increases f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Validation runs were carried out for MSR and MDR to validate the set of equations presented in Section 2. Results obtained from the computational model (i.e., continuity, momentum, energy, species, and reaction kinetics) of steam and dry methane reforming were validated against the experiential data obtained from Hoang 31 and Lu, 24 respectively. In the work of Hoang, 31 the reformer bed is of 10 mm inner diameter and 150 mm long and it is packed with nickel catalyst supported on gamma alumina.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation runs were carried out for MSR and MDR to validate the set of equations presented in Section 2. Results obtained from the computational model (i.e., continuity, momentum, energy, species, and reaction kinetics) of steam and dry methane reforming were validated against the experiential data obtained from Hoang 31 and Lu, 24 respectively. In the work of Hoang, 31 the reformer bed is of 10 mm inner diameter and 150 mm long and it is packed with nickel catalyst supported on gamma alumina.…”
Section: Model Validationmentioning
confidence: 99%
“…For simplicity, this study was carried out for exhaust gas reforming of methane (main constituent of natural gas) in a tubular packed bed reactor. This kind of reactor has been widely studied for both steam 21,22 and dry 23,24 methane reforming. The packed bed reactor adopted in this study is shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the endothermic ammonia decomposition reaction temperature is adjusted to be high ~550 • C for a considerable conversion. Nevertheless, the high reaction temperature does not only increase the exergy loss through the heat recuperation but also cause a large re-radiation loss [22,31,35]. Consequently, decreasing the ammonia decomposition temperature at a relatively high pressure is very critical to improve the efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The performance characteristics of the MRCR for H 2 production was studied using computational fluid dynamic (CFD) modeling in the present work. The use of CFD techniques in modeling packed bed reformer, with hydrogen membrane, for both laboratory and industrial application has been widely reported. CFD studies have also been used to understand combustion dynamics in industrial furnaces .…”
Section: Introductionmentioning
confidence: 99%